Initial development of precipitation and onset of cloud electrification in thunderstorms at Pune - KANDALGAONKAR, S. S.; TINMAKER , M. I. R.; MANOHAR, G. K. (MAUSAM, 1998)
Using one-minute interval data of electric field and the records of rainfall measured at the ground surface, time sequence in the initial registration of precipitation and the onset of cloud electrification was examined for a series of 14 thunderstorms of the year 1973 at Pune to study the relationship between the initial development of precipitation and intensification of cloud electrification. The combined result of the 14 storms studied, each of which yielded precipitation, indicated in-cloud development of precipitation at least 3-7 minutes in advance of onset of cloud electrification. It is inferred from the other supplementing studies published by other workers and from the above result that in most cases the precipitation development in thunderstorms is initiated well before the electric field begins to intensify. This result is in close agreement with the result of previous studies.